Spirometric changes in children with asthma exposed to environmental tobacco smoke and treated with inhaled corticosteroids - Radic, Snezana; Milenkovic, Branislava; Gvozdenovic, Branislav; Medjo, Biljana; Dimic Janjic, Sanja (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Corticosteroids are the most frequently prescribed anti-inflammatory treatment in asthma. A purpose of this study was to compare the spirometric parameters as a response to inhaled fluticasone propionate (FP) treatment in children with asthma, exposed and nonexposed to environmental tobacco smoke (ETS). Methods. The study included 527 children aged between 1 and 16 years with persistent asthma divided into the groups of ETS exposed (ETSE, n = 337) and ETS free (ETSF, n = 190) children. Spirometry was performed before (1st set of results) and after 6 months of FP treatment (2nd set of results). Good lung function (GLF) was defined as forced expiratory volume in one second (FEV1) ≥ 85%, and “poor lung function” (PLF) as FEV1 < 85%. Results. Among the ETSE children, 208 had one smoking parent, 129 had two, 228 had smoking mothers and 238 smoking fathers. The ETSE children received a higher FP dose (p < 0.0001) which was increased with the increase of the number of smokers in the family. The ETSE children had significantly lower lung function both in the 1st and 2nd sets of tests compared to the ETSF children (p < 0.05). After the FP treatment, both groups improved all spirometric parameters (p < 0.001). In the 2nd set of the spirometric tests, the children of smoking mothers had lower spirometry values compared to the children of smoking fathers (p < 0.05). The proportion of the children improving from the PLF to GLF after 6 months of FP was much higher among the ETSF than the ETSE children (p < 0.05). Conclusions. The ETSE children had lower spirometric values before FP. After 6-months of the FP treatment children in both groups improved the spirometric values, but the improvement was higher in the ETSF children.